6.8k views
5 votes
Consider the expression shown.

(x^-3 y^5 z^-4) • (x^6 y^-7 z^-2)


Part A. The value of the exponent of x in the simplified expression will be


1. -18


2. -9


3. 3


Part B. The value of the exponent of y in the simplified expression will be


1. -35


2. -12


3. -2


Part C. The value of the exponent of z in the simplified expression will be


1. -6


2. -2


3. 8

1 Answer

3 votes

Answer:

3, 3 and 1

Explanation:

Using the rule of exponents


a^(m) ×
a^(n) =
a^((m+n))

Given

(
x^(-3)
y^(5)
z^(-4) ×
x^(6)
y^(-7)
z^(-2)

A


x^(-3) ×
x^(6) =
x^((-3+6)) = x³ → with exponent 3

B


y^(5) ×
y^(-7) =
y^((5-7)) =
y^(-2) → with exponent - 2

C


z^(-4) ×
z^(-2) =
z^((-4-2)) =
z^(-6) → with exponent - 6

User Tasmin
by
5.2k points